ANALISIS EFISIENSI ALOKATIF FAKTOR-FAKTOR PRODUKSI SORGUM DI KABUPATEN GUNUNGKIDUL - Sandi Budi Arta; Dwidjono Hadi Darwanto; Irham Irham (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
This research aims to (1) determine the factors that influence the sorghum production in Gunungkidul District; (2) determine theallocative efficiency of sorghum production factors in Gunungkidul District. Number of respondents were 30 farmers chosen by purposive sampling. Analysis tools used in this research were the Cobb-Douglass Production Function and Allocative Efficiency Analysis. The result showed that the inputs such as land, seeds and organicfertilizerpositive affected to production of sorghum in Gunungkidul District. Result ofAllocative Efficiency analysis showedthat allocation ofland, seeds and organicfertilizer have not been efficient insorghum’sfarming in Gunungkidul District.